2022
DOI: 10.3390/ijms231911294
|View full text |Cite
|
Sign up to set email alerts
|

β-Klotho Promotes the Development of Intrauterine Adhesions via the PI3K/AKT Signaling Pathway

Abstract: Intrauterine adhesion (IUA) refers to injury to the basal layer of the endometrium, which can be caused by various factors. It is often accompanied by clinical symptoms such as abnormal menstruation, infertility, recurrent abortion, and periodic abdominal pain. In recent years, a number of studies have reported the effects of β-Klotho (KLB) on the occurrence and development of human tumors and fibrotic diseases, but its relationship with endometrial fibroblasts and endometrial fibrosis has not been elucidated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Pi3k and Akt are mainly expressed in inflammatory cells, vascular endothelial cells, and fibroblasts in the basal layer, spinous layer, and epithelial submucosa 10,11 . Limited Pi3k and Akt were observed in normal tissues (Figure 1E,F).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Pi3k and Akt are mainly expressed in inflammatory cells, vascular endothelial cells, and fibroblasts in the basal layer, spinous layer, and epithelial submucosa 10,11 . Limited Pi3k and Akt were observed in normal tissues (Figure 1E,F).…”
Section: Resultsmentioning
confidence: 98%
“…Pi3k and Akt are mainly expressed in inflammatory cells, vascular endothelial cells, and fibroblasts in the basal layer, spinous layer, and epithelial submucosa. 10,11 Limited Pi3k and Akt were observed in normal tissues (Figure 1E,F). In early stage OSF tissues, high levels of Pi3k and Akt expression are observed in the epithelial basal layer and submucosa.…”
Section: Inflammation and Collagen Level Increase As Osf Developsmentioning
confidence: 95%
“…Intrauterine adhesions caused by endometrial curettage or infection have been suggested to cause infertility [35]. If the basal layer of the endometrium is damaged during curettage, inflammation is triggered during the wound-healing process [36,37]. Patients with healed chronic endometritis have higher pregnancy and live birth rates than those with persistent inflammation [11]; therefore, healed inflammation in the uterus is important for improving pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%